2012
DOI: 10.1016/j.evolhumbehav.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural effects of color, but not morphological masculinity, on perceived attractiveness of men's faces

Abstract: Cross-cultural effects of color, but not morphological masculinity, on perceived attractiveness of men's faces SummaryMuch attractiveness research has focused on face shape. The role of masculinity (which for adults is thought to be a relatively stable shape cue to developmental testosterone levels) in male facial attractiveness has been examined, with mixed results. Recent work on the perception of skin color (a more variable cue to current health status) indicates that increased skin redness, yellowness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
139
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(159 citation statements)
references
References 60 publications
19
139
1
Order By: Relevance
“…Although the effect of colour was weaker than that of mouth curvature, faces with more yellow coloration were judged as looking healthier. This is consistent with prior work demonstrating a reliable preference for yellowness in faces [38,45,47,61], but additionally illustrates that yellowness acts independently of adiposity and mouth curvature as a cue to health in unaltered facial images. Our findings in 2D faces highlight the influence of colour and mouth curvatures (which is likely to be perceived as subtle expression) in judgements of health in a sample of young Caucasian adults.…”
Section: Discussionsupporting
confidence: 91%
“…Although the effect of colour was weaker than that of mouth curvature, faces with more yellow coloration were judged as looking healthier. This is consistent with prior work demonstrating a reliable preference for yellowness in faces [38,45,47,61], but additionally illustrates that yellowness acts independently of adiposity and mouth curvature as a cue to health in unaltered facial images. Our findings in 2D faces highlight the influence of colour and mouth curvatures (which is likely to be perceived as subtle expression) in judgements of health in a sample of young Caucasian adults.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to recent work focusing on comparing individuals from different populations (e.g., Little et al 2007;Stephen et al 2012;Tovée et al 2006), there has been a surge in work testing hypotheses via cross-cultural correlations. These studies have several merits (e.g., moving beyond unrepresentative, Western populations; Henrich et al 2010), but they also have several limitations.…”
Section: Resultsmentioning
confidence: 99%
“…shown that own-ethnicity faces are a better predictor for attractiveness judgements (Stephen et al, 2012), hence performing separate analyses for each ethnicity makes theoretical sense.…”
Section: Accepted Manuscriptmentioning
confidence: 99%